Students personal anxiety and their influence on the perception of social and psychological climate (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article describes the socio-psychological climate, factorsthat influence its perception, in particular, anxiety, presents the typesof socio-psychological climate and presents the results of a study of thepersonal anxiety of the student group (by C. Spielberg) and its impact onthe socio-psychological climate (by A. Fidler). The results of the study arehighlighted, how the students’ personal anxiety influences the perceptionof the social and psychological climate in the group.
Keywords: anxiety; personal anxiety; socio-psychological climate